2019
DOI: 10.1108/tr-05-2018-0062
|View full text |Cite
|
Sign up to set email alerts
|

Islamic and Muslim tourism: service quality and theme parks in the UAE

Abstract: Purpose The purpose of this paper is to identify dimensions of theme park quality from an Islamic perspective and develop a framework to examine the interrelationships between theme park service quality dimensions, visitor delight and visitor loyalty in theme parks in the United Arab Emirates (UAE). Design/methodology/approach The study is based on a detailed literature review and analysis of visitors’ comments on TripAdvisor.com about their experience in theme parks in the UAE. Findings Theme park service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…This evidence suggests that loyalty emerges, as hypothesized, as an overall evaluation that refers to an overall delight assessment of the relevant dimensions and associated delight attributes. This result also supports inline previous empirical research (Ahrholdt et al, 2016;Foroughi et al, 2019;Lari et al, 2019;Su et al, 2019). So then, the result of this study points that when customers of online ride hailing in D.I.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This evidence suggests that loyalty emerges, as hypothesized, as an overall evaluation that refers to an overall delight assessment of the relevant dimensions and associated delight attributes. This result also supports inline previous empirical research (Ahrholdt et al, 2016;Foroughi et al, 2019;Lari et al, 2019;Su et al, 2019). So then, the result of this study points that when customers of online ride hailing in D.I.…”
Section: Discussionsupporting
confidence: 91%
“…Although traditionally, many researchers argued that the important antecedent of loyalty is customer satisfaction. However, customer delight may be a more effective antecedent (Lari et al, 2019). It is exactly like (Torres et al, 2014) said that customer delight seems to occur as a result of feelable, reproducible, and positive memorable events that has a stronger influence on customer loyalty than satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past three decades, studies have explored how cultural factors influence consumer behaviour. As an important subcultural factor, religion plays a highly significant role in effecting consumer behaviour (Ahmad et al, 2015;Madni et al, 2016), because consumers exhibit their beliefs through their consumption choices (Lari et al, 2019). Past studies conceptualised religion as being a simple construct with religious affiliation (Mokhlis, 2009).…”
Section: Religiositymentioning
confidence: 99%
“…In a complementary line of research, Barber and Scarcelli (2010) identified cleanliness as an influencing factor of the perceived service quality. The more recent studies by Sun et al (2019) and Lari et al (2020) corroborate such finding by exploring two major online hospitality platforms, Airbnb and TripAdvisor, respectively. Additionally, since airport hotels are intrinsically connected to airports, issues related to transportation to the city center as well as flight related issues are also highly relevant from a service quality perspective (Tam et al, 2008).…”
Section: 2perceived Hotel Service Qualitymentioning
confidence: 60%